Inventory Of Plant Species of The Moraceae Family in The Sunan Gunung Djati State Islamic University Area - Silva Lupita; Sindi Nugrahani; Ateng Supriyatna (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
research with the aim of knowing the types of members of the Moraceae plant has been carried out in the area of ​​the Sunan Gunung Djati State Islamic University, Bandung. The method used is a survey by making direct observations at the research location. Data analysis was carried out descriptively. The results of the study obtained 2 types of plants belonging to Moraceae, namely Ficus benjamina and Artocarpus heterophyllus. The most common plants found were from the ficus genus with five species of Ficus benjamina. Abstrak: penelitian dengan tujuan mengetahui jenis-jenis anggota tumbuhan Moraceae telah dilakukan di kawasan Universitas Islam Negeri Sunan Gunung Djati Bandung. Metode yang digunakan adalah survei yaitu dengan melakukan pengamatan langsung di lokasi penelitian. Analisis data dilakukan secara deskriptif. Hasil penelitian diperoleh 2 jenis tumbuhan anggota Moraceae, yaitu Ficus benjamina dan Artocarpus heterophyllus. Tumbuhan yang paling banyak ditemukan adalah dari genus ficus dengan spesies Ficus benjamina sebanyak lima pohon. Kata kunci: Artocarpus, Ficus benjamina, Moraceae